Analisis Analisis Keuntungan Pengolahan Limbah Kulit Kopi Menjadi Pupuk Kompos di Pulau BeringinKabupaten OKU Selatan : Pengolahan Limbah Kulit Kopi menjadi Kompos - Atmo, Munsiarum; Mukhlisisn (Jurnal Bakti Agribisnis, 2025)
The purpose of this study was to calculate the amount of business income from processing coffee skin waste into compost in the Tunas Muda Farmer Group and analyze the profit level of the coffee skin waste processing business into compost in the Tunas Muda Farmer Group in Tanjung Kari Village, Beringin Island District, OKU Selatan Regency. This research was conducted in Tanjung Kari Village, Beringin Island Subdistrict, OKU Selatan Regency. The research location was chosen purposively with the consideration that in the village there is a farmer group that processes coffee skin waste into compost, namely the Tunas Muda Farmer Group. The research was conducted in February 2024. This research was conducted using the case study method. The sampling method used in this research is the census method. The sample amounted to 1 respondent from 1 population, namely the Tunas Muda Farmer Group which consists of 20 farmers where they process coffee skin waste into compost fertilizer. The results showed that the production cost of compost processing business from coffee skin waste KT. Tunas Muda in one production process is Rp 1,306,800, revenue is Rp 2,500,000 and income is Rp 1,193,200. The R/C ratio value is 1.91. The revenue BEP value of coffee skin waste compost processing business is Rp 205,400 with a revenue achievement value of Rp 2,500,000, the production BEP value is Rp 2,500,000, The production BEP value is 205 kg with a production achievement of 2,500 kg and a price BEP value of Rp 523/Kg with a price achievement of Rp 1,000/Kg, which shows that the business of processing compost fertilizer from coffee skin waste KT. Tunas Muda in Tanjung Kari Village, Beringin Island Sub-district, OKU Selatan Regency, is financially profitable to operate.